THE ROLE OF ARTIFICIAL INTELLIGENCE IN MODERN INVESTMENT MANAGEMENT (International Conference on Computing, Artificial Intelligence and Information Systems, 2026)
Artificial Intelligence (AI) has become a transformative force in modern investment management, reshaping traditional financial practices through advanced data analytics, machine learning algorithms, and automation. This study examines the role of AI in enhancing investment decision-making, portfolio optimization, risk assessment, and market forecasting. By processing large volumes of structured and unstructured data in real time, AI systems improve prediction accuracy and reduce human bias in financial analysis. The research also explores the growing use of algorithmic trading, robo-advisory services, and AI-powered risk management tools in global financial markets.Furthermore, the paper analyzes the advantages and challenges associated with AI integration, including increased efficiency, cost reduction, transparency, regulatory concerns, ethical considerations, and cybersecurity risks. The findings suggest that while AI significantly improves performance and operational efficiency in investment management, effective governance frameworks and human oversight remain essential to ensure sustainable and responsible financial innovation. Ultimately, AI is not replacing investment professionals but transforming their roles toward more strategic and analytical functions in the digital financial ecosystem.
Keywords: Artificial Intelligence (AI); investment management; machine learning; algorithmic trading; portfolio optimization; risk assessment; predictive analytics; fintech; digital finance; robo-advisory services.